Managing risk in construction projects and sustainability: evidence from Malaysia - Nasruddina, Adibah Syahirah; Mustapha, Mazlina (Primrose Hall Publishing Group, 2019)
Prior literature defines risk management as the process of identifying and analysing the project risks and choosing the appropriate actions to remove the threats from any project. It is claimed that there are many risks involved in construction projects because the construction life cycle is filled with different risks at different stages of project development. Once the risks are identified, it is necessary to develop the appropriate risk management responses to detect any ordinary causes to deal with them. Thus, this study aims to examine the technical risks involved in property development project. Specifically, this study examines the technical risk implemented by construction companies. In addition, the risk response taken by the companies are also investigated. The study employs a qualitative method, where interviews were conducted with the contractors and developers of the construction projects. The findings show that technical risks are important as they can greatly affect the completion of construction projects, such as inaccurate project design, frequent change of drawings, and a shortage of material. This study contributes to the literature related to the risk management of construction companies, and it provides information to the key project participants about the importance of adopting a systematic and effective risk management to ensure successful property development projects.